Acute cutaneous botryomycosis of the hands. (2020) - Singh, Angad; Cook, Courtney; Kollmann, Kaitlyn; Rajpara, Anand
Abstract: Botryomycosis is a rare bacterial infection which is most commonly caused by Staphylococcus aureus . It usually affects the skin but can also involve the viscera. The cutaneous form typically presents as ulcerated plaques or nodules that evolve over months to years to form discharging sinuses. As opposed to the norm for this uncommon infection, our case had a relatively acute presentation. A 44-year-old male with a history of relapsed mantle cell lymphoma, stem cell transplant and chronic graft versus host disease on immunosuppressive therapy presented with 2–3 week history of sores on his hands. Punch biopsy and subsequent pathological testing confirmed the diagnosis of botryomycosis. The patient was subsequently treated with clindamycin for 30 days and the lesions completely resolved. In this case report, we highlight the acute presentation of this relatively rare and usually chronic infectious disease.